Quality of hospital care for sick newborns and severely malnourished children in Kenya: A two-year descriptive study in 8 hospitals - Gathara, David (BioMed Central, 2011)
BACKGROUND: Given the high mortality associated with neonatal illnesses and severe malnutrition and the development of packages of interventions that provide similar challenges for service delivery mechanisms we set out to explore how well such services are provided in Kenya. METHODS: As a sub-component of a larger study we evaluated care during surveys conducted in 8 rural district hospitals using convenience samples of case records. After baseline hospitals received either a full multifaceted intervention (intervention hospitals) or a partial intervention (control hospitals) aimed largely at improving inpatient paediatric care for malaria, pneumonia and diarrhea/dehydration. Additional data were collected to: i) examine the availability of routine information at baseline and their value for morbidity, mortality and quality of care reporting, and ii) compare the care received against national guidelines disseminated to all hospitals. RESULTS: Clinical documentation for neonatal and malnutrition admissions was often very poor at baseline with case records often entirely missing. Introducing a standard newborn admission record (NAR) form was associated with an increase in median assessment (IQR) score to 25/28 (22-27) from 2/28 (1-4) at baseline. Inadequate and incorrect prescribing of penicillin and gentamicin were common at baseline. For newborns considerable improvements in prescribing in the post baseline period were seen for penicillin but potentially serious errors persisted when prescribing gentamicin, particularly to low-birth weight newborns in the first week of life. Prescribing essential feeds appeared almost universally inadequate at baseline and showed limited improvement after guideline dissemination. CONCLUSION: Routine records are inadequate to assess newborn care and thus for monitoring newborn survival interventions. Quality of documented inpatient care for neonates and severely malnourished children is poor with limited improvement after the dissemination of clinical practice guidelines. Further research evaluating approaches to improving care for these vulnerable groups is urgently needed. We also suggest pre-service training curricula should be better aligned to help improve newborn survival particularly.